Addressing organizational learning to increase readiness for physical activity promotion in seven German nursing homes - Lea-Sofie Hahn; Ansgar Thiel; Viola Dembeck; Daniel Haigis; Leon Matting; Rebekka Pomiersky; Gerhard W. Eschweiler; Andreas M. Nieß; Gorden Sudeck; Annika Frahsa (PLoS ONE, 2025)
Promoting physical activity among nursing home residents is essential for enhancing physical and mental well-being. However, organizational structures often prioritize basic care and indirectly hinder physical activity promotion. This study investigates organizational and individual learning processes to increase readiness for physical activity promotion in seven German nursing homes between 2020 and 2023. We selected a heterogeneous mix of nursing homes from the applications representing different forms of organizations regarding environmental contexts, capacity, care providers, and resident population composition. We used a mixed-methods approach for data collection, including interviews, documents, surveys, photologs, and fieldnotes. Data was treated confidentially and recorded pseudonymously. Applying qualitative content analysis, we revealed that physical activity promotion was initially insufficiently incorporated into organizational structures. Through a comprehensive assessment tool, we analyzed post-intervention changes in organizational readiness. Using a public management organizational learning model, we identified key processes that drove these changes. To maintain reflexivity, two authors analyzed data and discussed the results. Combining different data collection forms reduced the risk of researcher bias. Collaborating with external stakeholders helped validate the findings. Our findings highlight the significance of individual and organizational learning, which led to notable shifts: Individual learning improved staff awareness for the relevance of and competencies in physical activity promotion, as well as resident participation levels in actions offered. Organizational learning led to an adaptation of weekly activity schedules, modification of existing actions to promote PA in close alignment with home-specific needs, and the creation of PA-friendly infrastructures. Health-promoting leadership and shared values emerged as crucial factors in fostering a culture of physical activity promotion. Our study demonstrates the feasibility of promoting physical activity in nursing homes by integrating it into organizational structures and fostering a culture of readiness. This approach can enhance resident well-being and quality of life.